Generating longitudinal growth charts from preterm infants fed to current recommendations. Issue 6 (25th May 2020) - Young, Aneurin; Andrews, Edward T; Ashton, James John; Pearson, Freya; Beattie, R Mark; Johnson, Mark John
Abstract : Objective: To use repeated measurements of weight, length and head circumference to generate growth centile charts reflecting real-world growth of a population of very preterm infants with a well-described nutritional intake close to current recommendations. Design: Infants born before 30 weeks gestational age (GA) were recruited. Infants received nutrition according to an integrated care pathway, with nutrient intake recorded daily, weight recorded twice-weekly and length and head circumference weekly. The LMS method was used to construct growth centile charts between 24 and 36 weeks corrected GA for each parameter. Setting: A single tertiary neonatal unit in England. Patients: 212 infants (124 male) (median GA at birth: 27.3 weeks, median birth weight: 900 g). Results: Median daily energy, protein, carbohydrate and fat intake were within 3% of published recommendations. The total number of measurements recorded was 5944 (3431 for weight, 1227 for length and 1286 for head circumference). Centile charts were formed for each parameter. Data for male and female infants demonstrated similar patterns of growth and were pooled for LMS analysis. A web application was created and published (bit.ly/sotongrowth ) to allow infants to be plotted on these charts with changes in SD score of measurements reported and graphically illustrated. Conclusions: These charts reflect growth in a real-world cohort of preterm infants whose nutrient intakes are close to current recommendations. This work demonstrates the feasibility of forming growth charts from serial measurements of growing preterm infants fed according to current recommendations which will aid clinicians in setting a benchmark for achievable early growth.